2019
DOI: 10.1111/ejn.14582
|View full text |Cite
|
Sign up to set email alerts
|

Paternal transgenerational epigenetic mechanisms mediating stress phenotypes of offspring

Abstract: Depression and anxiety risk are highly influenced by both genetic and environmental factors. Recently, it has been proposed that epigenetic mechanisms may also contribute to the transmission of both depression-and anxiety-related behaviors across multiple generations. This review highlights long-lasting epigenetic alterations observed in offspring of fathers, including some distinct effects on male and female offspring, in animal models. Available evidence emphasizes how both the developmental time point and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 66 publications
4
40
0
Order By: Relevance
“…The paternal mode of the transgenerational modification of DA functions is consistent with our previous study [9], which identified a critical role of the paternal lineage in mediating non-genetic inheritance of social and fear-related abnormalities after MIA. The paternal mode of transmission is also consistent with other models of early-life adversities, such as prenatal or neonatal stress [40]. Hence, there is increasing evidence to suggest that stable epigenetic modifications in sperm cells may represent a mechanism by which exposure to environmental adversities, including immune challenges [40], can induce pathological effects across generations.…”
Section: Discussionsupporting
confidence: 74%
“…The paternal mode of the transgenerational modification of DA functions is consistent with our previous study [9], which identified a critical role of the paternal lineage in mediating non-genetic inheritance of social and fear-related abnormalities after MIA. The paternal mode of transmission is also consistent with other models of early-life adversities, such as prenatal or neonatal stress [40]. Hence, there is increasing evidence to suggest that stable epigenetic modifications in sperm cells may represent a mechanism by which exposure to environmental adversities, including immune challenges [40], can induce pathological effects across generations.…”
Section: Discussionsupporting
confidence: 74%
“…Evidence supporting the nongenetic inheritance of disease susceptibility as a result of adverse stress-induced epigenetic modifications to the parental germline continues to grow. 6 11 Results of the present study juxtapose these findings by showing for the first time, to the best of our knowledge, that exposure of adult mice to repetitive systemic hypoxia during adulthood—and prior to conception—protects against retinal ischemic injury in their adult F1-generation progeny. Thus, not only can disease burden be inherited across generations as a result of maladaptive responses on the part of parents, but progeny can also inherit disease resilience secondary to adaptive responses on the part of their parental lineage to beneficial stress stimuli that promote such phenotypes.…”
Section: Discussionsupporting
confidence: 67%
“…Accumulating evidence documents the intergenerational and transgenerational passage of phenotypes in a number of species, 6 8 including mammals. 9 11 That this also occurs in humans, beyond imprinting, is strongly suggested by a broad set of elegantly curated epidemiological data. 12 , 13 The vast majority of research in these aforementioned fields of study has focused on identifying pathological phenotypes and disease susceptibility resulting from previously presented adverse stressors.…”
mentioning
confidence: 99%
“…Evidence supporting the nongenetic inheritance of disease susceptibility as a result of environmentally-induced epigenetic modifications to the parental germline continues to grow (6)(7)(8)(9)(10)(11). conversely, passing the resilient phenotype to the F2 generation and beyond would be unnecessary if the potential for these subsequent generations to experience this injury is no longer present.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, epigenetic modifications secondary to stress and environmental change can not only affect phenotypes across the lifespan, but can also affect phenotypes in progeny. Accumulating evidence documents the intergenerational and transgenerational passage of epigenetically-induced phenotypes in a number of species (6)(7)(8), including mammals (9)(10)(11). That this also occurs in humans, beyond imprinting, is strongly suggested by a broad set of elegantly curated epidemiological data (12,13).…”
Section: Introductionmentioning
confidence: 99%